Serbia and Montenegro : Poverty Reduction Strategy Progress Reports; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note discusses the Poverty Reduction Strategy Progress (PRSP) Reports for Serbia and Montenegro. Although the strong economic growth in recent years in Serbia has improved average living standards, the reports note that its impact on poverty reduction remains inconclusive. The increases in real wages and pensions have boosted household incomes and consumption, according to the national accounts statistics. There are growing regional disparities, with Belgrade increasing its advantage over the rest of the country.